PAH-specific therapy for pulmonary hypertension and interstitial lung disease: A systemic review and meta-analysis - Ning Zhao; Jun Chen; Mingming Zhang; Lihui Zhou; Lisong Liu; Jie Yuan; Xingxue Pang; Dayi Hu; Xiaoxia Ren; Zhongyi Jin (Frontiers in Cardiovascular Medicine, 2022)
ObjectivePulmonary hypertension (PH) in context with interstitial lung disease (ILD) portends serious clinical consequences and a high rate of mortality. Recently published randomized controlled trials (RCTs) which assessed the pulmonary arterial hypertension (PAH)-specific drugs for pulmonary hypertension and interstitial lung disease (PH-ILD) revealed inconsistent clinical outcomes with previous studies. We conducted a systemic review and meta-analysis to further investigate the effect of PAH-specific therapies for PH-ILD.MethodsClinical trials were searched from the EMBASE, PUBMED, and CENTRAL databases. The duration from the establishment of the database to June 2022 for RCTs evaluates the effect of PAH-specific therapy in patients with PH-ILD. RevMan 5.4 was used for the meta-analysis.ResultsA total of six articles (with a total of 791 patients) were included, including 412 patients in the treated group and 379 patients in the control group. As compared to placebo, the change of 6MWD was a significant improvement with PAH-specific therapy in the six RCTs (23.09; 95% CI, 12.07–34.12 P < 0.0001); but when the study with inhaled treprostinil was excluded, the significant improvement in the change of 6MWD from baseline was not present anymore (MD 11.01, 95%CI−6.43–28.46 P = 0.22). There was no significant improvement in the change in lung function, hemodynamic parameters, clinical worsening, all-cause death, and serious adverse effects in the treated group compared to placebo.ConclusionPAH-specific therapy significantly improved exercise capacity in the patients with PH-ILD, but this is due to the greater contribution of the study with inhaled treprostinil. Therefore, our findings still did not support the routine use of the whole PAH-specific drugs for PH-ILD.